Association between body fat distribution and age at menarche: a two sample Mendelian randomization study - Xue, Peng; Wang, Dan; Chen, Yao; Tang, Jingyi; Chen, Yang; Mei, Hao; Lin, Cuilan; Liu, Shijian (Frontiers in Pediatrics, 2024)
Background: Numerous studies have examined the association between obesity and age at menarche (AAM), with most focusing on traditional obesity indicators such as body mass index. However, there are limited studies that explored the connection between body fat distribution and AAM, as well as a scarcity of Mendelian randomization (MR) studies. Methods: In this study, we conducted a two-sample MR study to evaluate the causal effects of eight body fat distribution indicators on AAM. Inverse variance weighted (IVW) method was used for primary analysis, while supplementary approaches such as MR-Egger and weighted median were also utilized. Considering that the eight exposures were highly correlated, we performed an MR Bayesian model averaging (MR-BMA) analysis to prioritize the effect of major exposure on AAM. A series of sensitivity analyses were also performed. Results: From a range of 82 to 105 single nucleotide polymorphisms (SNPs) were utilized as genetic instrumental variables for each of the exposure factors. After Bonferroni correction, we found that whole body fat mass (β: -0.17; 95% CI: -0.24, -0.11), left leg fat percentage (β: -0.14; 95%CI: -0.21, -0.07), left leg fat mass (β: -0.20; 95%CI: -0.27, -0.12), left arm fat percentage (β: -0.18; 95%CI: -0.26, -0.11) and left arm fat mass (β: -0.18; 95%CI: -0.26, -0.10) were associated with decreased AAM using random effects IVW method. And the beta coefficients for all MR evaluation methods exhibited consistent trends. MR-BMA method validated that left arm fat percentage plays a dominant role in AAM. Conclusions: Our MR study suggested that body fat has broad impacts on AAM. Obtaining more information on body measurements would greatly enhance our comprehension of pubertal development.